Composite lithium supplement agent and preparation method thereof, positive plate, lithium ion battery and electric equipment

By forming a carbon cladding layer with nitrogen doped elements outside the lithium-ion supplement core of the lithium-ion battery, the problem of poor electronic conductivity of the carbon cladding supplement lithium-ion supplement is solved, and the charging specific capacity and battery performance are improved.

CN120565600APending Publication Date: 2025-08-29BYD CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510012764.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing carbon-coated lithium supplement agents have low charging capacity in lithium-ion batteries, poor electronic conductivity, and are easy to react with water, resulting in performance not meeting the requirements of use.

Method used

A composite lithium supplement agent is used, the inner core is a lithium supplement agent, and the outer layer is a carbon coating layer doped with nitrogen elements, and the pyridine nitrogen content is greater than or equal to 50%. A uniform carbon coating layer is formed by chemical vapor deposition method to improve the ion and electron conductivity of the carbon coating layer.

Benefits of technology

The interaction between the carbon cladding layer and the lithium supplement core is enhanced, the charging specific capacity is optimized, the electrochemical performance and stability of the battery is improved, and the chemical stability and conductivity of the lithium supplement agent are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a composite lithium supplement agent and a preparation method thereof, a positive plate, a lithium ion battery and electric equipment, the composite lithium supplement agent comprises a lithium supplement agent core and a carbon coating layer coating the lithium supplement agent core, the carbon coating layer is doped with a nitrogen element, the nitrogen element comprises a pyridine type nitrogen element, and the pyridine type nitrogen element is a nitrogen element. The pyridine type nitrogen element accounts for more than or equal to 50% of the nitrogen element, the interaction between the carbon layer and the lithium supplement agent material is enhanced by doping nitrogen in the carbon coating layer, carriers can be provided for a carbon material conduction band on the surface layer of the lithium supplement agent, and the electronic conductivity of the carbon coating layer is improved, so that the capacity exertion of the lithium supplement agent is optimized; lone pair electrons of the pyridine type nitrogen element enable the pyridine type nitrogen element to become good coordination atoms and have very strong electron affinity, the chemical stability of the lithium supplementing agent can be improved by doping the pyridine type nitrogen element with high content ratio in the carbon coating layer, and the charging specific capacity of the lithium supplementing agent is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite lithium supplement and a preparation method thereof, a positive electrode sheet, a lithium ion battery and electrical equipment. Background Art

[0002] Adding a small amount of lithium supplement to the positive electrode can replenish active lithium and increase battery capacity. However, potential problems exist in the use of lithium supplements. Due to their poor electronic conductivity, they are highly polarized during decomposition and require a voltage higher than the theoretical decomposition potential to fully decompose. They also readily react with water and are prone to moisture absorption and failure when exposed to air. In the prior art, lithium supplements are typically carbon-coated to effectively improve their conductivity and overall battery performance. However, existing carbon-coated lithium supplements have low specific charge capacities when used in batteries and cannot meet usage requirements. Summary of the Invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application provides a composite lithium supplement and a preparation method thereof, a positive electrode sheet, a lithium ion battery and an electrical device.

[0004] In order to solve the above problems, the first aspect of the present application provides a composite lithium supplement agent, including a lithium supplement agent core and a carbon coating layer coated on the outside of the lithium supplement agent core, wherein the carbon coating layer is doped with nitrogen elements, and the nitrogen elements include pyridine-type nitrogen elements, and the content of the pyridine-type nitrogen elements in the nitrogen elements is greater than or equal to 50%.

[0005] The composite lithium supplement agent provided in the present application has the following effects: by doping nitrogen in the carbon coating layer, the interaction between the carbon coating layer and the lithium supplement agent core is strengthened, and carriers can be provided for the conduction band of the carbon material on the surface of the lithium supplement agent, thereby improving the ionic conductivity of the carbon coating layer and optimizing the capacity of the lithium supplement agent. The lone pair electrons of the pyridinic nitrogen element make it a good coordinating atom with a strong electron affinity. Doping the carbon coating layer with a high content of pyridinic nitrogen greater than or equal to 50% can improve the electronic conductivity of the carbon coating layer, thereby optimizing the charge capacity of the lithium supplement agent.

[0006] A second aspect of the present application provides a method for preparing a composite lithium supplement, characterized in that it includes the following steps: S1: providing a lithium supplement core; S2: forming a carbon coating layer doped with nitrogen on the surface of the lithium supplement core, wherein the nitrogen includes pyridinic nitrogen, and the pyridinic nitrogen accounts for greater than or equal to 50% of the nitrogen.

[0007] A third aspect of the present application provides a positive electrode sheet, comprising the composite lithium supplement described in the first aspect, or a composite lithium supplement prepared by the preparation method of the composite lithium supplement described in the second aspect.

[0008] A fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet described in the third aspect.

[0009] A fifth aspect of the present application provides an electrical device comprising the lithium-ion battery described in the fourth aspect. DETAILED DESCRIPTION

[0010] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] The present invention provides a composite lithium supplement agent, comprising a lithium supplement agent core and a carbon coating layer coated on the lithium supplement agent core, wherein the carbon coating layer is doped with nitrogen elements, wherein the nitrogen elements include pyridine nitrogen elements, and the content of pyridine nitrogen elements in nitrogen elements is greater than or equal to 50%.

[0012] Specifically, the lithium replenisher core has a high theoretical specific capacity and can be used as a positive electrode lithium replenisher material for lithium-ion batteries to compensate for the irreversible capacity loss during the battery's first cycle and improve the battery's cycle life. The nitrogen element exists in forms such as pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen. The lone pair electrons of pyridinic nitrogen make it a good coordinating atom with a strong electron affinity. The content of pyridinic nitrogen in the nitrogen element is greater than or equal to 50%, and can be, but is not limited to, 50%, 55%, 60%, 60.6%, 61.5%, 62.4%, 63.5%, 64.6%, 65.6%, 67.6%, 68.5%, 69.4%, 70.5%, 71.5%, 72.3%, 73.2%, 78.2%, 83.2%, 92.2%, 93.2%, 98%, etc.

[0013] The lithium supplement agent provided in the present application has the following effects: by doping nitrogen in the carbon coating layer, the interaction between the carbon coating layer and the lithium supplement agent material is strengthened, and carriers can be provided for the conduction band of the carbon material on the surface of the lithium supplement agent, thereby improving the ionic conductivity of the carbon coating layer and optimizing the capacity of the lithium supplement agent. The lone pair electrons of the pyridinic nitrogen element make it a good coordinating atom with strong electron affinity. Doping a high content of pyridinic nitrogen in the carbon coating layer can improve the electronic conductivity of the carbon coating layer, increase the chemical stability of the lithium supplement agent, and optimize the charge capacity of the lithium supplement agent.

[0014] In some preferred embodiments, the content of pyridinic nitrogen elements in the total nitrogen element is 50%-75%.

[0015] Specifically, the content of pyridinic nitrogen elements in nitrogen elements within this range can further enhance the ionic conductivity and electronic conductivity of the carbon coating layer, and further optimize the charge capacity of the lithium supplement agent.

[0016] In some embodiments, the nitrogen element further comprises graphitic nitrogen element and pyrrolic nitrogen element, the pyrrolic nitrogen element accounts for 10%-25% of the nitrogen element, and the graphitic nitrogen element accounts for 15%-25% of the nitrogen element.

[0017] Specifically, the inclusion of pyrrolic nitrogen and graphitic nitrogen in the coating layer enhances the ionic conductivity of the lithium supplement, effectively improving the conduction of lithium ions and thereby enhancing the electrochemical performance of the lithium supplement. The content of pyrrolic nitrogen in the nitrogen composition can be, but is not limited to, 10%, 10.3%, 11.4%, 12.5%, 13.6%, 14.7%, 15.8%, 16.8%, 17.5%, 18.3%, 19.1%, 20.5%, 22.2%, and 25%; the content of graphitic nitrogen in the nitrogen composition can be, but is not limited to, 15%, 16.5%, 17.3%, 18.1%, 18.6%, 19.2%, 20.2%, 20.6%, and 25%.

[0018] In some embodiments, the doping amount of nitrogen in the carbon coating layer is 1%-5%.

[0019] Specifically, the nitrogen doping level in the coating layer refers to the atomic percentage of nitrogen, or more specifically, the percentage of nitrogen atoms in the total carbon coating layer. Nitrogen doping within the aforementioned range can effectively increase the lithium ion and electron conductivity of the lithium supplement, thereby further improving the electrochemical performance and stability of the lithium supplement. Nitrogen doping levels can be, but are not limited to, 1%, 2%, 2.5%, 3%, 4%, and 5%.

[0020] In some preferred embodiments, the doping amount of nitrogen is 2.8%-4.3%.

[0021] Specifically, the nitrogen doping amount within this range can further improve the lithium ion conductivity of the carbon coating layer while maintaining the electrical conductivity of the carbon coating layer. The nitrogen doping amount can be, but is not limited to, 2.8%, 3.2%, 3.5%, 3.8%, 4.1%, and 4.3%.

[0022] In some embodiments, the carbon coating layer has a thickness of 50 nm to 500 nm.

[0023] Specifically, the thickness of the carbon coating layer can be, but is not limited to, 50 nm, 70 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 330 nm, 350 nm, 400 nm, 450 nm, or 500 nm. Within the aforementioned range, the carbon coating layer can effectively isolate the lithium supplement agent core from contact with water and carbon dioxide in the outside air, effectively inhibiting side reactions, while also improving the conductivity of the lithium supplement agent, increasing the lithium delithiation rate of the lithium supplement agent, and thereby improving its stability. The thickness of the carbon coating layer can be directly observed using a scanning electron microscope (SEM).

[0024] In some embodiments, the mass of the carbon coating layer accounts for 0.5%-2.0% of the mass of the composite lithium supplement agent.

[0025] Specifically, the mass percentage of the carbon coating layer within the above range can improve its interfacial stability, increase the decomposition efficiency of the lithium supplement agent, and also improve the electronic and ion conductivity, which helps to enhance the lithium supplement effect. The mass of the carbon coating layer can be, but is not limited to, 0.5%, 0.63%, 0.73%, 0.78%, 0.85%, 0.88%, 0.92%, 0.97%, 1.04%, 1.09%, 1.12%, 1.17%, 1.24%, 1.26%, 1.34%, 1.36%, 1.54%, 1.76%, 1.87%, 1.94%, and 2.0% of the mass of the composite lithium supplement agent.

[0026] In some embodiments, the Dv10 of the composite lithium supplement is 4.0 μm-5.5 μm, and / or the Dv50 of the composite lithium supplement is 7.5 μm-9.0 μm.

[0027] Specifically, the Dv10 of the composite lithium supplement refers to the particle size corresponding to the volume distribution percentage of the composite lithium supplement reaches 10%, and the Dv50 of the composite lithium supplement refers to the particle size corresponding to the volume distribution percentage of the composite lithium supplement reaches 50%; the Dv10 of the composite lithium supplement can be but is limited to 4.0μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, and 5.5μm, and the Dv50 of the composite lithium supplement can be but is limited to 7.5μm, 7.8μm, 7.9μm, 8.0μm, 8.1μm, 8.2μm, 8.3μm, 8.4μm, 8.5μm, 8.6μm, 8.7μm, and 9.0μm. The particle size of the composite lithium supplement agent is within the above range, which optimizes the contact area between the composite lithium supplement agent and the electrolyte, greatly improves the delithiation effect of the composite lithium supplement agent, and improves the kinetic performance of the composite lithium supplement agent, so that it can better play the role of lithium supplementation, accelerate the transmission rate of lithium ions, improve the interface contact with the electrode material, enhance the interface stability, reduce the polarization during the charge and discharge process, and thus improve the electrochemical performance of the battery.

[0028] In some embodiments, the specific surface area of ​​the composite lithium supplement is 1.2 m 2 / g-1.8m 2 / g.

[0029] Specifically, the specific surface area of ​​the composite lithium supplement can be, but is not limited to, 1.20 m 2 / g, 1.28m 2 / g, 1.30m 2 / g, 1.32m 2 / g, 1.34m 2 / g, 1.35m 2 / g, 1.37m 2 / g, 1.40m 2 / g, 1.42m 2 / g, 1.45m 2 / g, 1.47m 2 / g, 1.58m 2 / g, 1.69m 2 / g, 1.80m 2 / g, the specific surface area of ​​the composite lithium supplement agent is within the above range, which can accelerate the transmission rate of lithium ions, improve the kinetic performance of the lithium supplement agent, improve the interface contact with the electrode material, enhance the interface stability, reduce the polarization during the charge and discharge process, and thus improve the electrochemical performance of the battery.

[0030] In some embodiments, the lithium supplement core includes at least one of Li5FeO4, Li2NiO2, Li6CoO4, Li3N, LiSiO4, and Li2O.

[0031] Specifically, the lithium replenisher core can effectively compensate for the active lithium consumed by the formation of the negative electrode SEI film during the first charging of the battery, thereby effectively improving the first coulombic efficiency and cycle life of the battery; at the same time, the lithium replenisher core can also reduce the capacity attenuation of the battery during the cycle, maintaining the high capacity and good cycle stability of the battery.

[0032] In some embodiments, the lithium supplement core includes doping elements, and the doping elements include one or more of Mg, Ti, V, Cr, Mn, Ni, Co, Gu, Zn, Zr, Nb, Mo, Ta, Al, Si, Sn, Sb, Bi, La, and Ce.

[0033] Specifically, the use of the above-mentioned doping elements can stabilize the positive electrode interface of the lithium supplement agent after delithiation, improve the structural stability and thermal stability of the lithium supplement agent, enhance the kinetic performance of the lithium supplement agent, and thus improve the lithium supplement efficiency and performance of the battery.

[0034] In some preferred embodiments, the proportion of the doping element is less than 1.5%, where the proportion of the doping element refers to the atomic ratio of the doping element to the core of the lithium supplement agent.

[0035] In some preferred embodiments, the core of the lithium supplement comprises Li5FeO4, and the doping element comprises at least one of Ti and Al.

[0036] Specifically, Ti and / or Al doping can partially replace the iron ions in the crystal structure of the lithium supplement Li5FeO4, reduce the Li Frenkel defects in the lithium supplement lattice, and increase the Li + The concentration of vacancies increases the diffusion rate of Li ions during the insertion and extraction process, improves the kinetics of the lithium replenisher, and thus improves the lithium replenishment efficiency and performance of the battery.

[0037] In a second aspect, the present application provides a method for preparing a composite lithium supplement, comprising the following steps:

[0038] S1: providing the lithium supplement core;

[0039] S2: forming a carbon coating layer doped with nitrogen on the surface of the lithium supplement core, wherein the nitrogen includes pyridinic nitrogen, and the content of pyridinic nitrogen accounts for more than or equal to 50% of the nitrogen.

[0040] Specifically, the lithium supplement agent core provided in this application can be purchased or prepared independently. Specifically, the specific method for forming the nitrogen-doped carbon coating layer on the surface of the lithium supplement agent core is not particularly limited. Those skilled in the art can use conventional methods in the art to form the nitrogen-doped carbon coating layer on the surface of the lithium supplement agent core. As a preferred embodiment, the nitrogen-doped carbon coating layer can be formed on the surface of the lithium supplement agent core by chemical vapor deposition (CVD).

[0041] Chemical vapor deposition (CVD) is the process of depositing a thin film of material onto a substrate through a chemical reaction of gaseous substances. CVD allows for easy control of the carbon coating, nitrogen doping content, and thickness of the carbon coating, resulting in a more uniform coating and high coating efficiency. The process also uses simple equipment and is easily scalable.

[0042] In some embodiments, forming a nitrogen-doped carbon coating layer on the surface of the lithium supplement agent core includes first heating the lithium supplement agent core to 550°C to 850°C in an apparatus, then introducing a pyridine nitrogen source and a carbon source, and reacting at 550°C to 850°C for 10 minutes to 120 minutes to form a nitrogen-doped carbon coating layer on the surface of the lithium supplement agent core.

[0043] Compared with the prior art, the lithium supplement agent provided by this application uses chemical vapor deposition to assist in the synthesis of carbon-coated lithium supplement agent cores. The material phase purity is higher, XRD diffraction does not contain impurities, the content of the nitrogen source and carbon source introduced is easy to control, and the adsorbed gas is directly carbonized and coated on the surface of the lithium supplement agent core, thereby making the two more tightly bonded, which is conducive to improving the conductivity of the lithium supplement agent core; forming a uniform nitrogen-doped carbon coating layer, which can effectively inhibit the generation of residual alkali, and the nitrogen source used is a pyridine-like organic precursor, so that the obtained carbon coating layer has a high pyridine-type nitrogen element content, further optimizing the charge specific capacity of the lithium supplement agent. The method provided by this application has a simple preparation process, easy operation and control, and is easy to industrialize.

[0044] Specifically, the temperature of chemical vapor deposition is 550° C.-850° C., and the deposition time is 10 min-120 min.

[0045] Specifically, the chemical vapor deposition temperature can be, but is not limited to, 550°C, 600°C, 700°C, 800°C, or 850°C, and the chemical vapor deposition time can be, but is not limited to, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, or 120 minutes. Chemical vapor deposition temperature and time within the above ranges can further densify the carbon coating layer, enhance the bond between the carbon coating layer and the core, and increase the proportion of pyridinic nitrogen in the resulting carbon coating layer.

[0046] In some embodiments, the pyridinic nitrogen source includes at least one of pyridine, 2,6-lutidine, pyridinol, and 2-methylpyridine.

[0047] In some embodiments, the carbon source comprises at least one of ethanol, methane, ethane, propane, ethylene, propylene, and acetylene.

[0048] Specifically, in the present application, the pyridine nitrogen source includes at least one of pyridine, 2,6-lutidine, pyridinol, and 2-picoline. Pyridine, 2,6-lutidine, pyridinol, and 2-picoline are all rich in nitrogen and can be used as pyridine nitrogen sources. This makes it easy to generate a high content of pyridine-type nitrogen in the coating layer, and the operation is simple and easy to achieve. The above-mentioned carbon source includes at least one of ethanol, methane, ethane, propane, ethylene, propylene, and acetylene. It has a wide range of sources, a simple preparation process, and the prepared carbon coating has good effect.

[0049] In some embodiments, the gas flux of the pyridine nitrogen source and carbon source is 0.2 L / min to 2 L / min.

[0050] Specifically, the gas flux of the pyridine nitrogen source and the carbon source can be, but is not limited to, 0.2 L / min, 0.4 L / min, 0.6 L / min, 0.8 L / min, 1 L / min, 1.2 L / min, 1.5 L / min, and 2 L / min. When the gas flux of the pyridine nitrogen source and the carbon source is within this range, a uniform, compact coating layer with an appropriate thickness can be formed, and agglomeration of the lithium supplement agent particles is not likely to occur.

[0051] In some embodiments, the heating rate is 10° C. / min to 20° C. / min.

[0052] Specifically, the heating rate can be, but is not limited to, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, and 20°C / min.

[0053] In a third aspect, the present application provides a positive electrode sheet comprising the composite lithium supplement described in the first aspect, or the composite lithium supplement prepared by the preparation method of the composite lithium supplement described in the second aspect.

[0054] It should be noted that the positive electrode sheet provided herein includes the aforementioned composite lithium replenisher. Due to the composite lithium replenisher's high structural stability, good conductivity, and excellent cycling performance, the lithium replenisher exhibits excellent lithium replenishment. The resulting positive electrode sheet has high energy density and excellent cycling performance, facilitating widespread application of positive electrode materials. The positive electrode sheet includes a positive electrode current collector and a collection active material layer disposed thereon. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.

[0055] In some embodiments, the positive electrode current collector may be, but is not limited to, at least one of copper, aluminum, nickel, and stainless steel. In one embodiment of the present application, the positive electrode current collector may be aluminum foil.

[0056] In some embodiments, the positive electrode active material layer further includes a positive electrode conductive agent, which can increase the conductivity between the active materials and improve the electronic conductivity of the positive electrode sheet. Specifically, the positive electrode conductive agent may include, but is not limited to, at least one of graphite, carbon black, acetylene black, and graphene. In one embodiment of the present application, the positive electrode conductive agent may be graphite. In another embodiment of the present application, the positive electrode conductive agent may be carbon black.

[0057] In some embodiments, the positive electrode active material layer further includes a positive electrode binder, which can improve the binding ability of the components in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the positive electrode current collector. Specifically, the positive electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose, and styrene-butadiene latex. In one embodiment of the present application, the positive electrode binder can be polyvinylidene fluoride.

[0058] In some embodiments, the mass ratio of the positive electrode material, the positive electrode conductor, and the positive electrode binder is (90-98): (1-5): (1-5). Specifically, the mass ratio of the positive electrode material, the positive electrode conductor, and the positive electrode binder may be, but is not limited to, 92:4:6, 90:5:5, 94:3:3, 96:3:1, 97:1:2, or 98:1:1. In one embodiment of the present application, the mass ratio of the positive electrode material, the positive electrode conductor, and the positive electrode binder may be (90-96): (1-5): (1-3). In another embodiment of the present application, the mass ratio of the positive electrode material, the positive electrode conductor, and the positive electrode binder may be (94-98): (2-5): (3-5).

[0059] In a fourth aspect, the present application provides a lithium-ion battery comprising the positive electrode sheet described in the third aspect.

[0060] The lithium-ion battery provided in the present application includes the above-mentioned positive electrode sheet. The positive electrode sheet has high energy density, high cycle performance, and good conductivity, which increases the battery capacity and improves the battery cycle performance, and is conducive to the wide application of the battery.

[0061] In some embodiments, the lithium-ion battery provided in the present application further includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer provided on the surface of the negative electrode current collector. Specifically, the negative electrode current collector may include, but is not limited to, at least one of copper, aluminum, nickel, and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil. In one embodiment of the present application, the negative electrode active material layer includes a negative electrode active material, which may include, but is not limited to, at least one of silicon, tin, germanium, lithium, alloys thereof, and carbon materials. Among them, the carbon material may include, but is not limited to, at least one of non-graphitizable carbon, graphite, pyrolytic carbon, coke, and activated carbon. In one embodiment of the present application, the negative electrode active material may be a carbon material. In another embodiment of the present application, the negative electrode active material may be a silicon material.

[0062] In some embodiments, the negative electrode active material layer further includes a negative electrode conductive agent. The negative electrode conductive agent can increase the electrical conductivity between the active materials and improve electronic conductivity. Specifically, the negative electrode conductive agent may include, but is not limited to, at least one of graphite, carbon black, acetylene black, and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.

[0063] In some embodiments, the negative electrode active material layer further includes a negative electrode binder. The negative electrode binder can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the negative electrode current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose, and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride.

[0064] In some embodiments, the lithium-ion battery provided herein further comprises an electrolyte. At least a portion of the positive electrode sheet and at least a portion of the negative electrode sheet are immersed in the electrolyte. The electrolyte used herein is not particularly limited and can be, but is not limited to, any substance known in the art as a battery electrolyte.

[0065] In a fifth aspect, the present application provides an electrical device comprising the lithium-ion battery described in the fourth aspect.

[0066] The electrical equipment includes the battery described in any of the above embodiments. The electrical equipment provided in this application has high energy density, good cycle performance, high safety performance, excellent comprehensive electrochemical performance, and strong market competitiveness. Electrical equipment includes mobile phones, tablets, watches, VR glasses, vehicles, etc. In one embodiment of the present application, the battery can be used in a vehicle to improve the safety of vehicle electricity use and increase the service life of the car battery. In another embodiment of the present application, the battery can also be used in a mobile phone to increase the battery capacity of the mobile phone and improve the battery life and safety of use.

[0067] The present invention is further described in detail below by way of examples.

[0068] Example 1

[0069] This embodiment is used to illustrate the lithium supplement agent and its preparation method, positive electrode sheet, lithium ion battery and electrical equipment disclosed in the present invention, and includes the following steps:

[0070] (1) Preparation of lithium supplements

[0071] A lithium source (specifically lithium hydroxide): an iron source (specifically ferric oxide): an aluminum source (specifically aluminum oxide) is mixed with water at an atomic ratio of lithium: iron: aluminum of 5.1:1.0:0.05 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0072] The obtained precursor powder was calcined under nitrogen atmosphere at a temperature of 500°C for 5 hours; after natural cooling, it was ground at a speed of 500 rpm for 3 hours to obtain the lithium supplement core Li5FeO4;

[0073] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 0.4L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0074] Example 2

[0075] The difference between Example 2 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0076] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 0.6L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0077] Example 3

[0078] The difference between Example 3 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0079] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 0.8L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0080] Example 4

[0081] The difference between Example 4 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0082] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 1L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0083] Example 5

[0084] The difference between Example 5 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0085] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 1.2 L / min, a deposition temperature of 700°C, and a deposition time of 0.5 h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0086] Example 6

[0087] The difference between Example 6 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0088] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:3, a gas flux of 1L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0089] Example 7

[0090] The difference between Example 7 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0091] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:2, a gas flux of 1L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0092] Example 8

[0093] The difference between Example 8 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0094] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 2:1, a gas flux of 1L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0095] Example 9

[0096] The difference between Example 9 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0097] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 800°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 1L / min, a deposition temperature of 800°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0098] Example 10

[0099] The difference between Example 10 and Example 1 is that the conditions of the coating layer are different, as follows, and the rest are the same as Example 1.

[0100] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 600°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 1L / min, a deposition temperature of 600°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0101] Example 11

[0102] (1) Preparation of lithium supplements

[0103] A lithium source (specifically lithium hydroxide) and an iron source (specifically ferric oxide) are mixed with water at an atomic ratio of lithium to iron of 5.1:1.0 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0104] The obtained precursor powder was calcined under nitrogen atmosphere at a temperature of 500°C for 5 hours; after natural cooling, it was ground at a speed of 500 rpm for 3 hours to obtain the lithium supplement core Li5FeO4;

[0105] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyridine to ethanol of 1:1, a gas flux of 1L / min, a deposition temperature of 700°C, and a deposition time of 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0106] Example 12

[0107] (1) Preparation of lithium supplements

[0108] A lithium source (specifically lithium carbonate) and a cobalt source (specifically cobalt nitrate) are mixed with water at an atomic ratio of lithium to cobalt of 6.1:1.0 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0109] The obtained precursor powder was calcined under nitrogen atmosphere at a temperature of 500°C for 3 hours; after natural cooling, it was ground at a speed of 500 rpm for 3 hours to obtain the lithium supplement core Li6CoO4;

[0110] The obtained lithium supplement agent core Li6CoO4 was placed in a tubular furnace and heated to 700°C at a heating rate of 20°C / min; at the same time, a pyridine nitrogen source (specifically pyridine) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition. The volume ratio of pyridine and ethanol was 1:1, the gas flux was 1L / min, the deposition temperature was 700°C, and the deposition time was 0.5h. After natural cooling, a nitrogen-doped carbon-coated lithium supplement agent was obtained.

[0111] Comparative Example 1

[0112] (1) Preparation of lithium supplements

[0113] A lithium source (specifically lithium hydroxide): an iron source (specifically ferric oxide): an aluminum source (specifically aluminum oxide) is mixed with water in an atomic ratio of 5.1:1.0:0.05 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0114] The obtained precursor powder was calcined in a nitrogen atmosphere at a temperature of 500°C and a second calcination time of 5 hours. After natural cooling, it was ground for 3 hours at a speed of 500 rpm to obtain the lithium supplement core Li5FeO4.

[0115] Comparative Example 2

[0116] (1) Preparation of lithium supplements

[0117] A lithium source (specifically lithium hydroxide): an iron source (specifically ferric oxide): an aluminum source (specifically aluminum oxide) is mixed with water in an atomic ratio of 5.1:1.0:0.05 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0118] The obtained precursor powder was calcined in a nitrogen atmosphere at a temperature of 500°C for 5 hours. After natural cooling, it was ground for 3 hours at a speed of 500 rpm to obtain the lithium supplement core Li5FeO4.

[0119] The obtained lithium supplement agent core Li5FeO4 was placed in a tube furnace and heated to 700°C at a heating rate of 20°C / min; a carbon source (specifically ethanol) was introduced for chemical vapor deposition, the deposition temperature was 700°C, the deposition time was 0.5h, and the gas flux was 1L / min. After natural cooling, carbon-coated lithium supplement agent particles were obtained.

[0120] Comparative Example 3

[0121] (1) Preparation of lithium supplements

[0122] A lithium source (specifically lithium hydroxide): an iron source (specifically ferric oxide): an aluminum source (specifically aluminum oxide) is mixed with water in an atomic ratio of 5.1:1.0:0.05 to form a slurry, and the slurry is spray-dried and granulated to obtain a precursor powder;

[0123] The obtained precursor powder was calcined under nitrogen atmosphere at a temperature of 500°C for 5 hours; after natural cooling, it was ground at a speed of 500 rpm for 3 hours to obtain the lithium supplement core Li5FeO4;

[0124] The obtained lithium supplement agent core Li5FeO4 was placed in a tubular furnace and heated to 800°C at a heating rate of 20°C / min; a nitrogen source (specifically pyrrole) and a carbon source (specifically ethanol) were introduced for chemical vapor deposition, with a volume ratio of pyrrole to ethanol of 1:1, a deposition temperature of 800°C, a deposition time of 0.5h, and a gas flux of 1L / min. After natural cooling, nitrogen-doped carbon-coated lithium supplement agent particles were obtained.

[0125] (2) Preparation of batteries:

[0126] The lithium supplement prepared in the above Examples 1-12 and Comparative Examples 1-3 was used as the positive electrode material to prepare a button battery. The above positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1 and evenly coated on aluminum foil to prepare a positive electrode sheet (the electrode mixing, coating and other preparation processes were all completed at a dew point of less than -30°C). The negative electrode sheet used a metal lithium sheet, the electrolyte used 1 mol / L LiPF6, and the solvent was EC:DMC:EMC=1:1:1 (volume ratio). In a vacuum glove box, the battery case, positive and negative electrode sheets, diaphragm (PE double-layer ceramic diaphragm), spring fragment, and gasket were assembled into a button battery.

[0127] Electrochemical performance test:

[0128] The battery was charged at a constant current of 0.066C using the LAND battery test system. The charging cut-off voltage of the lithium supplement was 4.2V, and the initial charge specific capacity of the battery was recorded.

[0129] Residual alkali test:

[0130] Weigh 0.5000g of sample and add 100ml of anhydrous ethanol. Filter with filter paper and rinse the filter paper with anhydrous ethanol for more than three times to ensure that the ions fully enter the filtrate and adjust the volume to 100ml. Use a potentiometric titrator to titrate to obtain the residual alkali content.

[0131] Carbon coating mass ratio test:

[0132] The carbon and sulfur analyzer was used for testing and JY / T017 general rules for elemental analyzer methods were quoted. The test method referred to GB / T14265-2017 general rules for analysis of hydrogen, oxygen, nitrogen, carbon and sulfur in metallic materials.

[0133] Test of nitrogen content and nitrogen type in lithium supplement coating layer:

[0134] X-ray photoelectron spectroscopy (XPS) was used to characterize the nitrogen content and nitrogen type in the carbon coating.

[0135] Lithium supplement specific surface area test:

[0136] The specific surface area of ​​the lithium supplement was tested by nitrogen adsorption method, and the test method referred to the standard GB / T 13390-2008 Determination of specific surface area of ​​metal powders - Nitrogen adsorption method.

[0137] Particle size analysis of lithium supplements:

[0138] The particle size distribution of lithium supplement was tested using a laser particle size analyzer, and the test method referred to the standard ISO13320-1:20178.

[0139] Carbon coating thickness test:

[0140] The results were obtained by direct observation of the bulk material using scanning electron microscopy (SEM) and high-resolution TEM.

[0141] The above test data are shown in Table 1.

[0142] By comparing the residual alkali content and the initial charge specific capacity of the composite lithium supplement in Comparative Example 1 and Comparative Example 2, Example 1, Example 2, Example 3, Example 4, and Example 5, it can be seen that doping with a high content of pyridinic nitrogen and increasing the thickness of the coated carbon layer can effectively inhibit the generation of residual alkali on the surface of the lithium supplement. In addition, an appropriate carbon layer thickness can effectively improve the specific capacity. However, an excessively thick carbon layer will reduce the proportion of active material, thereby causing a decrease in specific capacity. Comparison of Example 4, Example 6, Example 7, and Example 8 shows that the higher the nitrogen content in the nitrogen-doped carbon layer, the higher the specific capacity of the lithium supplement. This is mainly because nitrogen doping strengthens the interaction between the carbon layer and the lithium supplement material, and can also provide carriers for the conduction band of the carbon material on the surface of the lithium supplement, thereby improving the electronic conductivity of the carbon coating layer and optimizing the capacity of the lithium supplement. Furthermore, the effect is better when the content of pyridinic nitrogen in the nitrogen element is within the range of 50%-75%. Pyridinic nitrogen doping plays an important role in improving the capacity of the battery. From the comparison between Example 4 and Comparative Example 3, it can be seen that the specific capacity of the pyridine-type nitrogen-doped carbon-coated lithium supplement material is lower than the residual alkali content of the pyrrole-type nitrogen-doped carbon-coated lithium supplement, and the battery's first charge specific capacity is high because the pyridine-type nitrogen element can form a reversible nitrogen-containing lithium ion compound with lithium ions, thereby optimizing the capacity of the lithium supplement.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0144] Table 1

[0145]

[0146]

Claims

1. A composite lithium supplement agent, comprising a lithium supplement agent core and a carbon coating layer coated on the lithium supplement agent core, wherein the carbon coating layer is doped with nitrogen, wherein the nitrogen comprises pyridinic nitrogen, and the pyridinic nitrogen accounts for greater than or equal to 50% of the nitrogen.

2. The composite lithium supplement according to claim 1, characterized in that The content of the pyridinic nitrogen element in the nitrogen element is 50%-75%.

3. The composite lithium supplement according to claim 2, characterized in that The nitrogen element further includes graphite nitrogen element and pyrrole nitrogen element. The content of the pyrrole nitrogen element accounts for 10%-25% of the nitrogen element, and the content of the graphite nitrogen element accounts for 15%-25% of the nitrogen element.

4. The composite lithium supplement according to any one of claims 1 to 3, characterized in that In the carbon coating layer, the doping amount of the nitrogen element is 1%-5%.

5. The composite lithium supplement according to any one of claims 1 to 4, characterized in that The thickness of the carbon coating layer is 50nm-500nm.

6. The composite lithium supplement according to any one of claims 1 to 5, characterized in that: The mass of the carbon coating layer accounts for 0.5%-2.0% of the mass of the composite lithium supplement agent.

7. The composite lithium supplement according to any one of claims 1 to 6, characterized in that: The Dv10 of the composite lithium supplement is 4.0 μm-5.5 μm, and / or the Dv50 of the composite lithium supplement is 7.5 μm-9.0 μm.

8. The composite lithium supplement according to any one of claims 1 to 7, characterized in that: The specific surface area of ​​the composite lithium supplement is 1.2m 2 / g-1.8m 2 / g.

9. The composite lithium supplement according to any one of claims 1 to 8, characterized in that: The lithium supplement core includes at least one of Li5FeO4, Li2NiO2, Li6CoO4, Li3N, LiSiO4, and Li2O.

10. The composite lithium supplement according to any one of claims 1 to 9, characterized in that: The lithium supplement core includes doping elements, and the doping elements include one or more of Mg, Ti, V, Cr, Mn, Ni, Co, Gu, Zn, Zr, Nb, Mo, Ta, Al, Si, Sn, Sb, Bi, La, and Ce.

11. A method for preparing a composite lithium supplement, characterized in that: The following steps are involved: S1: Provide lithium supplement core; S2: forming a carbon coating layer doped with nitrogen on the surface of the lithium supplement core, wherein the nitrogen includes pyridinic nitrogen, and the content of the pyridinic nitrogen in the nitrogen is greater than or equal to 50%.

12. The composite preparation method of the lithium supplement according to claim 11, characterized in that: The forming of a carbon coating layer doped with nitrogen on the surface of the lithium supplement agent core comprises: The lithium supplement agent core is heated to 550° C. to 850° C. in the equipment, and then a pyridine nitrogen source and a carbon source are introduced. The reaction is carried out at 550° C. to 850° C. for 10 min to 120 min, thereby forming a carbon coating layer doped with nitrogen on the surface of the lithium supplement agent core.

13. The method for preparing the composite lithium supplement according to claim 12, characterized in that: The pyridine nitrogen source includes at least one of pyridine, 2,6-lutidine, pyridinol and 2-methylpyridine.

14. The method for preparing the composite lithium supplement according to claim 12 or 13, characterized in that: The carbon source includes at least one of ethanol, methane, ethane, propane, ethylene, propylene and acetylene.

15. The method for preparing the composite lithium supplement according to any one of claims 12 to 14, characterized in that: The gas flux of the pyridine nitrogen source and the carbon source is 0.2 L / min to 2 L / min.

16. The method for preparing the composite lithium supplement according to any one of claims 12 to 15, characterized in that: The heating rate is 10°C / min to 20°C / min.

17. A positive electrode sheet, characterized in that: The invention relates to a composite lithium supplement according to any one of claims 1 to 10, or a composite lithium supplement prepared by the preparation method of the composite lithium supplement according to any one of claims 11 to 16.

18. A lithium ion battery, characterized in that: Including the positive electrode sheet according to claim 17.

19. An electrical device, characterized in that: Including the lithium ion battery according to claim 18.

Citation Information

Cited By

  • Lithium supplement agent and preparation method thereof, positive plate, battery, battery pack and electric equipment

    CN121215941A

  • Composite lithium replenishing agent and preparation method therefor, positive electrode sheet, lithium-ion battery, and electric device

    WO2026145344A1